Frecuencia De Utilización De Los Gestos Técnicos Del Portero De Fútbol Prejuvenil Durante Su Acción Competitiva (2016)
In this research the technical actions of football goalkeeper prejuvenil category are characterized for their competitive activity. The focus of this research is quantitative, with a descriptive scope and a non-experimental design, where the systematic, valid and reliable record of the behavior of a goalkeeper prejuvenil category was performed using observational methodology for six games, after it was made his respective statistical analysis using SPSS V21 software. The results showed that the most common actions during the competition were the defensive type (58.5%), the action more defensive technique used by the goalkeeper was the collection (19.8%), while the technical action more offensive he used was the kick (18.2%). Among the most important findings are that the type of technical action most frequently used by football goalkeeper prejuvenil category are defensive technical actions, averaging 42.33 per game, the main technical actions, used by the goalkeeper, found the collection technique defensive action, with an average of 14.33 per game; I followed the technique is found offensive action kick, with an average of 13.1 per game.